2008
DOI: 10.1021/ja806846q
|View full text |Cite
|
Sign up to set email alerts
|

Protein Conformational Transitions: The Closure Mechanism of a Kinase Explored by Atomistic Simulations

Abstract: Kinase large-scale conformational rearrangement is an issue of enormous biological and pharmacological relevance. Atomistic simulations able to capture the dynamics and the energetics of kinase large-scale motions are still in their infancy. Here, we present a computational study in which the atomistic dynamics of the "open-to-closed" movement of the cyclin-dependent kinase 5 (CDK5) have been simulated. Simulations were carried out using a new sampling method that is able to find the lowest free-energy channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
147
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 71 publications
18
147
1
Order By: Relevance
“…In the ADA case, assuming that the initial and the final state correspond to ADA with the H3 α-helix in the closed and open conformation, respectively, a PCV is constructed with the cartesian coordinates of the alpha carbons of the residues that determine the α-helix movement. This type of CV has been successfully applied in recent studies on complex protein motion (29,30) and ligand/protein docking (20).…”
Section: Resultsmentioning
confidence: 99%
“…In the ADA case, assuming that the initial and the final state correspond to ADA with the H3 α-helix in the closed and open conformation, respectively, a PCV is constructed with the cartesian coordinates of the alpha carbons of the residues that determine the α-helix movement. This type of CV has been successfully applied in recent studies on complex protein motion (29,30) and ligand/protein docking (20).…”
Section: Resultsmentioning
confidence: 99%
“…[45] To reconstruct the freeenergy surface of the two copper dimers, we used well-tempered (WT) metadynamics, proved to be effective in previous studies, [46][47][48][49] within the framework of PLUMED. [50] Gaussians of 0.2 kcal mol À1 in height were deposited at one picosecond time interval, with a bias factor of 10.…”
Section: Metadynamics (Md)mentioning
confidence: 99%
“…This need is less stringent when enhanced sampling methods are combined with a multiple-replica approach, as in the case of the parallel-tempering metadynamics simulations approach (PTmetaD) (28,31). Indeed, it has been shown that PT-metaD is able to converge very complex conformational free-energy surfaces of kinases as a function of a few relevant variables (32,33).…”
mentioning
confidence: 99%